Leptomeningeal metastasis in breast cancer – a systematic review - Scott, Brian J. (Oncotarget, 2015)
BACKGROUND: There is limited data on the impact of specific patient characteristics, tumor subtypes or treatment interventions on survival in breast cancer LM. METHODS: A systematic review was conducted to assess the impact of hormone receptor and HER-2 status on survival in breast cancer LM. A search for clinical studies published between 1/1/2007 and 7/1/2012 and all randomized-controlled trials was performed. Survival data from all studies are reported by study design (prospective trials, retrospective cohort studies, case studies). RESULTS: A total of 36 studies with 851 LM breast cancer subjects were identified. The majority (87%) were treated with intrathecal chemotherapy. Pooled median overall survival ranged from 14.9-18.1 weeks depending on study type. Breast cancer LM survival (15 weeks) was longer than other solid tumor LM 8.3 weeks and lung cancer LM 8.7 weeks, but shorter than LM lymphoma (15.4 versus 24.2 weeks). The impact of hormone receptor and HER-2 status on survival could not be determined. CONCLUSIONS: A median overall survival of 15 weeks in prospective studies of breast cancer LM provides a historical comparison for future LM breast cancer trials. Other outcomes including the impact of molecular status on survival could not be determined based on available studies.